2016
DOI: 10.4236/ojpc.2016.63006
|View full text |Cite
|
Sign up to set email alerts
|

Investigate the Corrosion Inhibition of Mild Steel in Sulfuric Acid Solution by Thiosemicarbazide

Abstract: Corrosion inhibition of mild steel in 0.5 mol/L H2SO4 was investigated in the absence and presence of different concentrations of thiosemicarbazide. The inhibition efficiency of thiosemicarbazide was studied by electrochemical impedance methods, potentiodynamic polarization and scanning electron microscopy at different inhibitor concentrations. Inhibition efficiency, corrosion rate and surface coverage were evaluated at different concentrations of thiosemicarbazide. Electrochemical impedance plots indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The EP’s representational I – V curves demonstrated three distinct zones respective to pitting, polishing, and gas development on the anode surface, which varied depending on the voltage applied. Table shows the polarization curves acquired by gradually increasing the cell current and measuring the steady-state anode, as well as the I L calculated by extrapolating linear sections of the solubility potential to the crossing of the congruous solubility current. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The EP’s representational I – V curves demonstrated three distinct zones respective to pitting, polishing, and gas development on the anode surface, which varied depending on the voltage applied. Table shows the polarization curves acquired by gradually increasing the cell current and measuring the steady-state anode, as well as the I L calculated by extrapolating linear sections of the solubility potential to the crossing of the congruous solubility current. , …”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the polarization curves acquired by gradually increasing the cell current and measuring the steady-state anode, as well as the I L calculated by extrapolating linear sections of the solubility potential to the crossing of the congruous solubility current. 10 , 39 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be interpreted from the Nyquist plots that the pattern of impedance curves was not affected by the inhibitors [54]. It should be noted that the Nyquist plots displayed a divergence from the ideal semicircles that could be due to frequency dispersion affected by non-homogeneity or roughness of metal surface during metal dissolution [55,56]. The impedance spectra also showed that the semicircle and the diameters incremented with an increase in the concentration of inhibitors.…”
Section: Corrosion Inhibition Performance Measured Using Electrochemi...mentioning
confidence: 99%